PB12. Improved pattern separation after spermidine supplementation in older individuals with subjective cognitive decline: Proof-of-concept study. Issue 8 (August 2018) - Wirth, M.
Abstract : Background: Subjective cognitive decline, a risk factor of Alzheimer's disease, was previously associated with subtle alterations in the hippocampus, a potential target for early intervention. This proof-of-concept human trial evaluated impacts of a novel dietary spermidine supplementation on hippocampus-dependent memory functions in individuals at increased risk for Alzheimer's disease. Methods: Healthy older participants with subjective cognitive decline and self-reported worry ( n  = 30, mean age: 70 ± 5 years, 2 drop-outs) were included in the 3-months randomized, placebo-controlled, double-blind trial. Episodic memory was assessed using a behavioral paradigm known to involve the hippocampal formation. Behavioral performance, measured using a recognition memory and a pattern separation score, was compared between intervention groups (polyamine and placebo) at the end of intervention, co-varying for baseline levels. Results: Pattern separation, but not recognition memory, was enhanced in the spermidine compared to placebo-treated group at the end of intervention with a medium effect size (Cohen's d  = 0.74). Within group comparisons indicated improvement of pattern separation performance in the spermidine-treated (Cohen's d  = 0.80) and not in the placebo-treated (Cohen's d  = 0.20) group. A similar effect was not observed for recognition memory performance. Discussion: Spermidine supplementation may induce positive effects in pattern separation, an early behavioral marker of memory changes associated with Alzheimer's dementia. This finding allows for longer-term intervention studies in humans to investigate impacts of oral spermidine intake on episodic memory and hippocampal integrity. The spermidine-rich plan extract could perhaps increase reserve mechanisms in older individuals at risk for Alzheimer's disease.